2023
DOI: 10.3390/jcm12030912
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy: Soluble and Imaging Ocular Biomarkers

Abstract: Diabetic retinopathy (DR), the most common microvascular complication of diabetes mellitus, represents the leading cause of acquired blindness in the working-age population. Due to the potential absence of symptoms in the early stages of the disease, the identification of clinical biomarkers can have a crucial role in the early diagnosis of DR as well as for the detection of prognostic factors. In particular, imaging techniques are fundamental tools for screening, diagnosis, classification, monitoring, treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 207 publications
0
2
0
Order By: Relevance
“…HRF are defined as discrete, circular, scattered, and well-demarcated highsignal lesions observed on OCT [19] . Research has identified the presence of HRF in diseases such as diabetic macular edema (DME) [20][21] , AMD [22] , retinal vascular occlusions [23][24] , central serous chorioretinopathy (CSC) [25] , and degenerative retinal diseases [26] . The exact clinical and pathological mechanisms of HRF are not yet fully understood, but they are closely related to lipid exudation and translocated retinal pigment epithelial cells in DME, as well as macrophages, microglial cells, and degenerated photoreceptor cells in AMD [27] .…”
Section: Overview Of Hyperreflective Focimentioning
confidence: 99%
“…HRF are defined as discrete, circular, scattered, and well-demarcated highsignal lesions observed on OCT [19] . Research has identified the presence of HRF in diseases such as diabetic macular edema (DME) [20][21] , AMD [22] , retinal vascular occlusions [23][24] , central serous chorioretinopathy (CSC) [25] , and degenerative retinal diseases [26] . The exact clinical and pathological mechanisms of HRF are not yet fully understood, but they are closely related to lipid exudation and translocated retinal pigment epithelial cells in DME, as well as macrophages, microglial cells, and degenerated photoreceptor cells in AMD [27] .…”
Section: Overview Of Hyperreflective Focimentioning
confidence: 99%
“…Optical Coherence Tomography (OCT) is a non-invasive test to acquire bidimensional images of the different retinal layers, and optical coherence tomography angiography (OCTA) is a novel diagnostic tool to observe the microvasculature of the retina and choroid without the need for dye injection [8]. Since changes in choroidal thickness, retinal thickness, vessel density of the superficial capillary plexus, and deep capillary plexus can be signs of endothelial damage and dysfunction, OCTA could also be a valid modality to detect diabetic-induced abnormalities [9][10][11][12]. Another useful test is in vivo corneal confocal microscopy (IVCCM), a non-invasive and reproducible technique that allows for the study of the living human cornea, including the cellular structure, as well as sub-basal nerve plexus [13,14].…”
Section: Introductionmentioning
confidence: 99%